(untitled) (Bangladesh Journal of Nuclear Agriculture, 2026)
Rice blast, caused by Magnaporthe oryzae, poses a significant threat to rice cultivation worldwide, particularly in Bangladesh where rice is a major staple cereal. This study explores the biocontrol potential of bacterial isolates against rice blast disease, with an emphasis on in vitro and field efficacy. Thirty bacterial isolates from indigenous rice varieties and rhizospheric soils were evaluated using dual culture techniques to assess their antagonistic effects on M. oryzae. Six isolates demonstrating significant antifungal activity were further tested in field trials through seed and seedling priming methods. Results indicated that these bacterial isolates significantly reduced leaf blast incidence and severity, with specific isolates (Isolate 2 and Isolate 5) showing notable efficacy. Yield was significantly influenced by bacterial treatments, with seed priming using Isolate 5 (358.20 g/m²) and seedling priming using Isolate 2 (342.98 g/m²) achieving the highest yields, significantly outperforming the control (128.72 g/m²). This study highlights the effectiveness of biocontrol agents in enhancing rice production and offers a sustainable strategy for disease management in rice. Bangladesh J. Nuclear Agric,39(2): 123-135, 2025